2017
DOI: 10.1007/s10549-017-4378-2
|View full text |Cite|
|
Sign up to set email alerts
|

Pro-apoptotic effect of Δ2-TGZ in “claudin-1-low” triple-negative breast cancer cells: involvement of claudin-1

Abstract: Claudin-1 overexpression and Δ2-TGZ treatment are associated to apoptosis in MDA-MB-231 and Hs578T "claudin-1-low" TNBC. Moreover, in MDA-MB-231 cells, claudin-1 is involved in the pro-apoptotic effect of Δ2-TGZ. Our results suggest that claudin-1 re-expression could be an interesting therapeutic strategy for "claudin-1-low" TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Thus, the re-expression of claudin 1 in MDA-MB-361 breast cancer cells induces apoptosis [20]. Our team demonstrated that claudin 1 overexpression leads to apoptosis in MDA-MB-231 and Hs578T "claudin 1 low" TNBC cells after 48 h [21]. Claudin 1 is also involved in cell motility and migration [9].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Thus, the re-expression of claudin 1 in MDA-MB-361 breast cancer cells induces apoptosis [20]. Our team demonstrated that claudin 1 overexpression leads to apoptosis in MDA-MB-231 and Hs578T "claudin 1 low" TNBC cells after 48 h [21]. Claudin 1 is also involved in cell motility and migration [9].…”
Section: Introductionmentioning
confidence: 82%
“…Hs578T cells were grown in DMEM medium containing phenol red (Life technologies) supplemented with 10% FCS, 2 mM l-glutamine and 10 µg/mL bovine insulin. MCF-10A cells were maintained in DMEM/F12 (GIBCO) supplemented with 5% horse serum, 1% l-glutamine 1% penicillin/streptomycin and a mix of EGF (epidermal growth factor), cholera toxin, hydrocortisone and insulin [21].…”
Section: Breast Cancer-derived Cells Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Differential interference contrast microscopy images were then obtained randomly ( Peng et al, 2018 ). The ratio of Hoechst positive cells and Tunel positive cells were respectively calculated and at least five images of each sample in different visions were observed ( Geoffroy et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%